Utilisation of natural wastes: Water-resistant semi-transparent paper for food packaging. (1st September 2022) - Hosen, Md Dulal; Hossain, Md Shebbir; Islam, Md Azharul; Haque, Abu Naser Md Ahsanul; Naebe, Maryam
Abstract: Use of non-degradable plastics in food packaging is alarming for the environment as they are often thrown away after short consumption. Though papers are replacing plastics in different sectors, their low water resistance limits their use in food packaging. in the past, water-resistant papers have been fabricated, but the natural degradability of the paper has been compensated. This study proposes water-resistant yet biodegradable papers from naturally abundant wastes, such as banana plant (BP) and water hyacinth (WH) and validates their properties for practical packaging uses. The resources were completely used, avoiding generation of any in-process biomass residue. This study for the first time reports the impact of ethyl cellulose (EC) coating (∼10 μm) on paper surfaces. The morphology and chemical analysis of the coated papers confirmed the consistent formation of EC layer on paper surfaces. The presence of EC significantly reduced the vapour transmission (22–30%) and moisture content (6–11%) of the papers. Water drops were stable on the coated surfaces at least for 20 min and then were wiped off leaving a dry surface. EC coating considerably increased the tensile index, i.e., 13–17% for BP and 20–35% for WH, though elongation and modulus properties remained almost unchanged. All the papers showed ultraviolet (UV)-resistance, while the coated papers were more transparent in the visible light region. Overall results confirmed the potential of the proposed EC-coated papers as a promising alternative to single-use plastics in food packaging. Graphical abstract: Image 1 Highlights: Water-resistant yet bio-friendly paper was made by ethyl cellulose (EC) coating. Banana plant and water hyacinth were utilised as low-cost source of paper making. Water drops were resisted by coated surface for at least 20 min. Tensile index and transparency improved by coating though vapour transport reduced.